Perkembangan Industri Roti Winda dan Raffi Heppy Bakery di Balai Baru Kecamatan Kuranji Kota Padang Tahun 2010-2022 - Putri, Marchelina Nurfa; Najmi, Najmi (Jurnal Kronologi, 2025)
This research discusses the development of the Winda & Raffi Heppy Bakery bread industry in Balai Baru, Kuranji District, Padang City, 2010-2022. The problem of this research is the background to the establishment and development of the Winda & Raffi Heppy Bakery bread industry from 2010-2022. The aim of this research is to reveal how the Winda & Raffi Heppy Bakery bread industry is developing in Balai Baru Padang City. This research is a qualitative descriptive research using historical methods, namely: (1) heuristic, namely collecting data from oral and written sources. This data was obtained through company archives and interviews with informants, namely Mr. Alius and Mrs. Izur, bakery factory workers and neighbors of the factory environment, (2) source criticism was used to determine the suitability of the source to be used, (3) interpretation of the data that had been collected, (4) historiography is writing scientific research in the form of a thesis. The results of this research show that experience is a very important factor in starting a business. With experience, job opportunities open up. The bakery industry is experiencing good development starting from the number of workers and in the production process. Apart from that, the establishment of the bakery industry also improves the economic welfare of families, workers and individuals, making it possible to meet the needs of life better.